2017
DOI: 10.1037/xhp0000327
|View full text |Cite
|
Sign up to set email alerts
|

Generalized movement representation in haptic perception.

Abstract: The extraction of spatial information by touch often involves exploratory movements, with tactile and kinesthetic signals combined to construct a spatial haptic percept. However, the body has many tactile sensory surfaces that can move independently, giving rise to the source binding problem: when there are multiple tactile signals originating from sensory surfaces with multiple movements, are the tactile and kinesthetic signals bound to one another? We studied haptic signal combination by applying the tactile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…The median score over subjects was 0.93 and was significantly different from the 0.5 chance level (two-tailed sign test: p = 0.004). This result replicated our previous findings 22 , 28 .
Figure 5 ( a ) Mean ratio of responses for each subject in the baseline condition corresponding to the between hands transfer hypothesis (Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The median score over subjects was 0.93 and was significantly different from the 0.5 chance level (two-tailed sign test: p = 0.004). This result replicated our previous findings 22 , 28 .
Figure 5 ( a ) Mean ratio of responses for each subject in the baseline condition corresponding to the between hands transfer hypothesis (Fig.
…”
Section: Resultssupporting
confidence: 93%
“…The perceived orientation of the triangle resulted from the expansions or contractions of the tactile bar combined with the movements of the hand. In a subsequent study we showed that this type of information transfer generalised to different limbs 28 .
Figure 2 ( a ) Truth table of triangle orientations corresponds to the integration between one movement and one tactile stimulus in the baseline condition (between hands transfer).
…”
Section: Introductionmentioning
confidence: 76%
“…In Experiment 4, the speed discrimination task was randomly alternated with a secondary control task similar to the one used by Dupin, Hayward, and Wexler (2017), to ensure that participants maintained the fixation on the central cross. The control task involved Landolt-like stimuli, consisting in a gray square with either the left or the right side missing (Michelson contrast: 17%).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…Any body movement produces concomitant cutaneous sensations, so movement and tactile stimulation are inextricably linked [ 12 , 13 ]. However, it remains unclear whether and how movement information affects tactile perception on body parts that do not move.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, relative localization of nearby tactile stimuli should be unaffected by such transformations. However, the spatial transformation may differ between two successive tactile stimulations because of the automatic integration of a concurrent displacement vector, even when the displacement is irrelevant and spatially remote [ 13 , 23 ]. In our case, the two successive tactile stimuli would use different remapping transformations, producing biases even in relative localization judgement.…”
Section: Discussionmentioning
confidence: 99%